Basic Computer Architecture and Quantitative Techniques in Computer Design Instruction Pipeline ,Arithmetic Pipeline, Hazards ,Exception and Interrupts - Sardar, Rupam (INTERANTIONAL JOURNAL OF SCIENTIFIC RESEARCH IN ENGINEERING AND MANAGEMENT, 2024)
We talk about the quantitative approach to computer architecture in this paper. We also go over Amdahl's Law, scalability, parallelism, and the principle of locality in relation to quantitative measurement. We also demystify computer architecture by focusing on smart technical design and cost- performance-power trade-offs. In the context of computer architecture, we think the field has continued to develop and move toward the exacting quantitative foundation of venerable scientific and technical disciplines. The pipelining principles in processor design are the focus of this study.The fundamentals of the instruction pipeline are covered, and an example-based explanation of how to reduce a pipeline delay is provided.The primary goal is to comprehend how a processor's pipeline functions.The different risks that lead to pipeline deterioration are described, along with ways to reduce them. Architecture-based development environments are emerging as a useful tool for building reliable distributed systems. By means of the abstract characterization of intricate software Software reuse and evolution are encouraged in terms of system topologies that involve the interface- level interaction of software parts. Furthermore, as evidenced by research findings in the field of software architecture, it becomes possible to offer formal annotations for the accurate characterization of configuration behavior together with related CASE tools for automated analysis. Nevertheless, while being essential to attaining software resilience, software fault tolerance—and specifically exception management in that context—has received little attention. Keywords: Instruction Pipeline ,Arithmetic Pipeline, Hazards